2004
DOI: 10.1021/tx0498253
|View full text |Cite
|
Sign up to set email alerts
|

A QSAR for Baseline Toxicity:  Validation, Domain of Application, and Prediction

Abstract: The interest in modeling and application of structure-activity relationships has steadily increased in recent decades. It is generally acknowledged that these empirical relationships are valid only within the same domain for which they were developed. However, model validation is sometimes neglected, and the application domain is not always well-defined. The purpose of this paper is to outline how validation and domain definition can facilitate the modeling and prediction of baseline toxicity for a large datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 63 publications
(93 reference statements)
2
39
0
Order By: Relevance
“…In fact we, like other authors [33][34][35][36][37][38], are strongly convinced, from personal experience, that models with high estimated ''predictivity'', highlighted only by internal validation methods, can be less predictive and even unpredictive when verified on new chemicals not used in developing the model [4].…”
Section: Internal and External Validationsupporting
confidence: 51%
“…In fact we, like other authors [33][34][35][36][37][38], are strongly convinced, from personal experience, that models with high estimated ''predictivity'', highlighted only by internal validation methods, can be less predictive and even unpredictive when verified on new chemicals not used in developing the model [4].…”
Section: Internal and External Validationsupporting
confidence: 51%
“…Others applied the concept of narcosis to aquatic toxicology, establishing the relationship between octanol-water partition coefficient (logP o/w ) and acute toxicity by narcosis (51)(52)(53). McFarland later showed that aquatic toxicity can be considered the result of penetration of toxicant into biophases and its interaction with one or more biochemical sites of action (54). Bioavailability of chemicals in aquatic organisms was shown to relate to absorption; for example, chemical partitioning across fish gills (55) represents an important route of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…According to the funnel hypothesis [20], in mixtures containing a large number of chemicals, the compounds are more possible to exhibit a baseline mechanism of action, thus the risk assessment should be based on the hypothesis of concentration addition. For this reason, baseline toxicity from ECOSAR program (also known as narcosis or nonspecific toxicity) was used for PNEC calculations [11,21,22]. It is necessary to be noted that the groups of perfluorinated compounds and siloxanes were not taken into account for the calculation of RQ mix , since, as it has been mentioned before, the toxicity of these chemicals cannot be predicted by ECOSAR model.…”
Section: Environmental Risk Assessmentmentioning
confidence: 99%